Detection and molecular characterization of cosavirus in adults with diarrhea, Thailand - Khamrin,P. (Springer Netherlands, 2015)
Human cosavirus (HCoSV) is a newly discovered virus in Picornaviridae family. At present it is not clear whether HCoSV is associated with diseases, including gastroenteritis in humans, as epidemiological data is limited. Epidemiological surveillance of HCoSV was conducted on 150 fecal specimens collected from children and 150 samples from adults with diarrhea in Thailand by RT-PCR screening. HCoSV was found in a single adult specimen and not in any of the fecal specimens from children. This represents the first report of HCoSV infection in patients with diarrhea in Thailand. Extensive epidemiological surveillance of novel viruses associated with diarrhea in other populations may provide a better understanding of the distribution, genetic diversity, and association of the viral agents associated with acute gastroenteritis in humans. © Springer Science+Business Media, LLC 2011.